2010
DOI: 10.1186/1472-698x-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Debate: Limitations on universality: the "right to health" and the necessity of legal nationality

Abstract: BackgroundThe "right to health," including access to basic healthcare, has been recognized as a universal human right through a number of international agreements. Attempts to protect this ideal, however, have relied on states as the guarantor of rights and have subsequently ignored stateless individuals, or those lacking legal nationality in any nation-state. While a legal nationality alone is not sufficient to guarantee that a right to healthcare is accessible, an absence of any legal nationality is almost c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 26 publications
0
36
0
6
Order By: Relevance
“…Kingston et al [31] have described in detail the difficulty Roma face in accessing healthcare without the necessary documents. In addition, this research has shown that 18.9% (95% confidence interval = 15.3 - 22.5%) of Roma do not have health insurance cards compared to both the general population, 9.8% (95% confidence interval = 8.8 - 10.8%), and poorest quintile, 5.6% (95% confidence interval = 5.2 - 6.0%).…”
Section: 0 Resultsmentioning
confidence: 99%
“…Kingston et al [31] have described in detail the difficulty Roma face in accessing healthcare without the necessary documents. In addition, this research has shown that 18.9% (95% confidence interval = 15.3 - 22.5%) of Roma do not have health insurance cards compared to both the general population, 9.8% (95% confidence interval = 8.8 - 10.8%), and poorest quintile, 5.6% (95% confidence interval = 5.2 - 6.0%).…”
Section: 0 Resultsmentioning
confidence: 99%
“…This discrepancy arises from the ''statelessness'' of many Roma (Kingston et al, 2010) as well as from the fact that due to social and economic reasons, many Roma do not declare their ethnic origin (Karaman, 2009;Kó sa and Adá ny, 2007).…”
mentioning
confidence: 99%
“…Accordingly, health systems and their governments, in order to guarantee the right to health, should work on the social and environmental determinants of health, derived from the form of organization of production in society, and the inequalities that exist in it, emphasizing that the action on these factors should be the responsibility of all State sectors (2) , considering the complexity of this right, as it achieves several spheres, including health, law, financial, educational, technological, housing, sanitation and management pol-icies (17) . Thus, the right to health has been closely related to other human rights such as human dignity, life, nondiscrimination, equity, prohibition against torture, privacy, access to information, and freedom for organizing associations, meetings, and movements (18) .…”
Section: Central Nucleusmentioning
confidence: 99%
“…In the Brazilian constitution, citizenship is guaranteed in three areas: civil, social and political rights. Hence, the civil rights of individual freedom preservation, such as contract, property, expression, conscience; political rights of representation and participation; and social rights, which are aimed at avoiding the worst effects of capitalism, with the right to health, education, food, labor, housing, leisure, safety, social security, maternity and child protection, and assistance to the disadvantaged were related to the citizen's condition (18) . In short, the term citizenship has contemplated the rights, obligations, as well as respect to the laws that the citizen has in relation to the country where he/she was born or chose to live in.…”
Section: Central Nucleusmentioning
confidence: 99%